2012
DOI: 10.1021/es204368u
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Dechlorination of Carbon Tetrachloride by Hydrophobic Green Rust Intercalated with Dodecanoate Anions

Abstract: The reductive dechlorination of carbon tetrachloride (CT) by Fe(II)-Fe(III) hydroxide (green rust) intercalated with dodecanoate, Fe(II)(4)Fe(III)(2)(OH)(12)(C(12)H(23)O(2))(2) · yH(2)O (designated GR(C12)), at pH ~ 8 and at room temperature was investigated. CT at concentration levels similar to those found in heavily contaminated groundwater close to polluted industrial sites (14-988 μM) was reduced mainly to the fully dechlorinated products carbon monoxide (CO, yields >54%) and formic acid (HCOOH, yields >6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…A study also shows that 0.3% magnetite in aquifer sediment was responsible for the natural attenuation of cis-dichloroethene (cis-DCE) in a groundwater plume [395]. A recent study has reported CCl4 degradation by different minerals with the normalized rate constant in the order of Fe 0 > GR > Fe(II) sorbed goethite > magnetite [396]. Another study found the rate constants for cis-DCE degradation in the order of GR > Fe(OH)2 > mackinawite = magnetite [397].…”
Section: Sewage Sludge Stabilization Soil Improvement Soil Sedimenmentioning
confidence: 99%
“…A study also shows that 0.3% magnetite in aquifer sediment was responsible for the natural attenuation of cis-dichloroethene (cis-DCE) in a groundwater plume [395]. A recent study has reported CCl4 degradation by different minerals with the normalized rate constant in the order of Fe 0 > GR > Fe(II) sorbed goethite > magnetite [396]. Another study found the rate constants for cis-DCE degradation in the order of GR > Fe(OH)2 > mackinawite = magnetite [397].…”
Section: Sewage Sludge Stabilization Soil Improvement Soil Sedimenmentioning
confidence: 99%
“…The rate of CCl 4 degradation on pyrite was slower than on FeS, but still faster than the other Fe(II)‐containing minerals. Ayala‐Luis et al () summarized carbon tetrachloride degradation by different minerals with the normalized rate constant in the order of Fe(0) > green rust > Fe(II) sorbed goethite > magnetite.…”
Section: Abiotic Degradation Mechanisms Involving Chlorinated Solventsmentioning
confidence: 99%
“…As a result, abiotic reductive dechlorination by minerals has attracted considerable attention within the research community (e.g., Butler and Hayes ; Elsner et al ; Han et al ; Jeong and Hayes , ; Jeong et al ; Tratnyek et al ). Abiotic transformation of carbon tetrachloride (CT), trichloroethane (TCA), TCE, and PCE has been investigated by a number of research groups using reactive iron minerals such as pyrite, troilite, mackinawite (Butler and Hayes ; Choi et al ; Hansson et al ; Lee and Batchelor , ; Kim et al ), vivianite (Bae and Lee ), magnetite (Lee and Batchelor ), and green rusts (Ayala‐Luis et al ; Lee and Batchelor ; Liang and Butler ; O'Loughlin et al ). Additionally, several field‐related studies have provided evidence that reactive iron minerals, such as iron sulfides and magnetite, may have important contributions to the degradation of chlorinated solvents in natural and engineered systems (Butler et al ; Darlington et al , ; Davis et al ; Devlin and Muller ; Ferrey et al ; Kennedy et al ; Kenneke and Weber 2003; Shen and Wilson ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large amount of green rust (GR) (color of the mixture was green, and confirmed via XRD; see Fig. S2) was formed at the end of the first phase due to the formation of highly reactive Fe(II)-Fe(III) layered double hydroxides [42]. In the second phase, nitrite (formed in the first phase) was rapidly reduced by Fe 0 (in excess Fe 0 condition) or dissolved Fe 2+ .…”
Section: Relationship Between Pb 2+ Removal Performance and Orp Variamentioning
confidence: 89%